Absence of antimicrobial activity of Euphorbia milii molluscicidal latex (Journal of Pharmaceutical Negative Results, 2012)
Introduction: Euphorbia milii latex has been used as herbal medicine and provedto be a potent plant molluscicide. Materials and Methods: The susceptibility ofStaphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa to E. milii molluscicidallatex was evaluated by assays in the agar well diffusion method and tubes dilution, todetermine the minimal inhibitory concentration and minimal bactericidal concentration.Results: Latex in natura (fresh) and lyophilized in a maximum viable concentrationof 100 mg/L did not show any inhibitory effect on the growth of the bacterial strainstested. Conclusion: Although it has been effective as a molluscicide, this latex presenteda total absence of antimicrobial activity in the two forms and concentrations tested.